How to prevent the detrimental effects of two months of bed-rest on muscle, bone and cardiovascular system: an RCT. Issue 1 (December 2017) - Kramer, Andreas; Gollhofer, Albert; Armbrecht, Gabriele; Felsenberg, Dieter; Gruber, Markus
Abstract Physical inactivity leads to a deconditioning of the skeletal, neuromuscular and cardiovascular system. It can lead to impaired quality of life, loss of autonomy, falls and fractures. Regular exercise would be a logical remedy, but the generally recommended high-volume endurance and strength training programs require a lot of time and equipment. In this randomized controlled study with 23 healthy participants, we established that a short, intensive jump training program can prevent the large musculoskeletal and cardiovascular deconditioning effects caused by two months of physical inactivity during bed rest, particularly the loss of bone mineral mass and density, lean muscle mass, maximal leg strength and peak oxygen uptake. The jump training group showed no significant changes with respect to these indicators of musculoskeletal and cardiovascular health after 60 days of bed rest, whereas the control group exhibited substantial losses: up to −2.6% in tibial bone mineral content and density, −5% in leg lean mass, −40% in maximal knee extension torque and −29% in peak oxygen uptake. Consequently, we recommend jump training as a very time-efficient and effective type of exercise for astronauts on long-term space missions, the elderly and sedentary populations in general.